2004
DOI: 10.1117/1.1691029
|View full text |Cite
|
Sign up to set email alerts
|

Optical biopsy of bone tissue: a step toward the diagnosis of bone pathologies

Abstract: In vivo absorption and reduced scattering spectra of the human calcaneous from 650 to 1000 nm were assessed using a laboratory system for time-resolved transmittance spectroscopy. Measurements were performed on the calcaneous of seven female volunteers ranging from 26 to 82 years of age. The analysis of the absorption spectra, using a linear combination of the key tissue absorbers (bone mineral, water, lipids, oxy- and deoxyhemoglobin), revealed a general decrease in bone mineral content and an increase in lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
140
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 31 publications
14
140
1
Order By: Relevance
“…In reference to the problem of osteoporosis, interesting results were reported by light scattering techniques showing correlation between osteoporosis and bone scattering coefficient 8 . Preliminary in vivo optical measurements on 5 volunteers done on calcaneous bone 9 showed interesting correlation between age, various tissue constituents (lipid, collagen, hemoglobin) and the scattering coefficient using a time-resolved broadband laboratory-based system 10 Bone fibrous tissue structure consists of connective tissue, proteins (mostly collagen) and blood cells as major components. The concentration of collagen and other tissue constituents could be related to bone physiological condition and to alterations induced by pathologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In reference to the problem of osteoporosis, interesting results were reported by light scattering techniques showing correlation between osteoporosis and bone scattering coefficient 8 . Preliminary in vivo optical measurements on 5 volunteers done on calcaneous bone 9 showed interesting correlation between age, various tissue constituents (lipid, collagen, hemoglobin) and the scattering coefficient using a time-resolved broadband laboratory-based system 10 Bone fibrous tissue structure consists of connective tissue, proteins (mostly collagen) and blood cells as major components. The concentration of collagen and other tissue constituents could be related to bone physiological condition and to alterations induced by pathologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The range around 750nm is absorbed mostly because of water, lipids and deoxyhemoglobin. [4] It was observed that with the increase in calcium density the output voltage increases.…”
Section: Infraredmentioning
confidence: 97%
“…In clinical practice, bone mineral density is usually expressed as a T score (number of standard deviations from the young normal mean) or Z score. [4] Negative value means the person suffers from the dieses while the positive values indicates no risk of fracture. Generally the value is between -3 to 3.…”
Section: T-scorementioning
confidence: 99%
“…The inorganic matrix contains calcium hydroxyapatite, which is responsible for the compressive strength of bone, and osteocalcium phosphate. The main components of the organic matrix are collagen, proteins, blood cells, and lipids [23]. The amount of bone mineral matrix is 16%, the lipid content is 54%, the proteins content is 16%, and water contributes 16% [23].…”
Section: Bone Structure and Physical Propertiesmentioning
confidence: 99%